Climate Change Impact and Frequency of Cyclone Surge in Bangladesh Coast: Proper Plan to Address Sustainably - Md. Bazlar Rashid; A.J.M Emadul Haque; Muhammad Abdul Aziz Patwari (International Journal of Economic and Environment Geology, 2022)
The Bay of Bengal (BoB) is a familiar ground for tropical cyclones. Consequently, cyclone surge and tidal inundation are very common in the Bangladesh coast which causes massive loss of human lives and properties. The present paper is an attempt to delineate the frequency of cyclones in the BoB, and loss of human lives and properties of Bangladesh coast on the basis of published reports, open source data and field checking, and finally to propose an effective way out to protect the area from cyclone surge. This study exposes that the frequency of cyclones in the area increased recently due to rise of global temperature. It further reveals that though the frequency of cyclones is increased, the loss of human lives is significantly decreased. Death toll in the last two decades decreased a lot for similar strength of cyclones comparing to the toll in last thirty or fifty years. Improvement in the early warning system, evacuation plan with proper training and construction of good number of cyclone shelter all over the coastal region are the main reason for this improvement. Though the loss of human lives is significantly reduced, the loss of economic resources in the coastal areas of the country is enormous as in earlier episodes. Therefore, adaptation for the Climate Change effect is needed to expedite with afforestation in the coastal region. Economic loss might also be reduced obstructing the cyclonic surge in the coastal region. Considering the cyclone path and tidal amplitude of cyclonic surge, upgradation or reconstruction of the coastal embankments all along the coast is essential. In this process, it is important to ensure that the tidal channels act as an inlet and outlets all over the coast to keep the natural processes active. An integrated approach including geoscientists, engineers, planners, policy makers, etc. is required to protect the resources as well as proper management of the coastal areas of the country.